IMPLEMENTASI KINERJA BAGIAN HUMAS DALAM MENYEBARLUASKAN INFORMASI TENTANG PROGRAM SPIRIT 99 HARI KERJA WALIKOTA MALANG - Aris Arlinda, Silvi; Prasetya Widodo, Herru (Jurnal Komunikasi Nusantara, 2019)
This study aimed to find out how the implementation of the Public Relations Officers in disseminating information about the Spirit 99 Days Work Program from the city Mayor of Malang, and to find out what obstacles occured in the implemention. This study used a qualitative method and the determination of respondents used a snowball sampling. The data collection techniques were through interviews, observation, documentation and the data analysis techniques included reduction, presentation, and verification. From the results of the study showed that the implementation of the public relations performance department in disseminating information, seen from the organization was effective and efficient. In the preparation of the public relations department did two approaches, namely based on the quantity and quality of its human resources, but in a communication policy Public Relations Section has not yet applied the basic tasks of government public relations. Directing the Public Relations Section was through formal and informal forms. While the supervision was through the IMM (Intelligence Media Management) software system which can monitor, collect online, printed and TV media content. From the assessment, the public relations department got some big problems with the existence of Spirit 99Work Days programs that have not been implemented. The inhibiting factors were inadequate funding and human resources and also the ineffective communication.